(untitled) (Superficies y Vacío, 2024)
Colloidal suspensions of carbon nanostructures (CNSs) were prepared by laser fragmentation in various liquid media using heat-treated coffee grounds as carbon precursor. A study by calorimetry was done in powder of waste coffee grounds to determine the temperature of obtaining carbon. The experiments were carried out in two stages, the first one consisted in obtaining the carbon source, for which powder of waste coffee grounds was thermally treated in air. The as-obtained carbon was characterized by scanning electron microscopy, energy dispersive X-ray spectroscopy, Raman spectroscopy and infrared spectroscopy. In the second step the as-obtained carbon was separately dispersed in four liquid media (acetone, toluene, methanol and isopropyl alcohol) to be fragmented by using a ns-pulsed Nd:YAG laser at its 1064 nm fundamental emission. The morphological features of the carbon nanostructures were obtained by transmission electron microscopy, while the optical properties of the colloidal suspensions were characterized by UV-Vis and photoluminescence spectroscopies. Results indicate that carbon nanostructures are successfully obtained in the four liquid media after the fragmentation process. The four colloidal suspensions show photoluminescent properties, which are seen to depend on the liquid medium nature. We found that the liquid medium also influences the efficiency of the laser fragmentation.